Virulence of nematodes against larvae of the south-American fruit fly in laboratory using soil from Porto Amazonas, Paraná, Brazil, as substrate - Foelkel,Ester (2016)
ABSTRACT: Anastrepha fraterculus is an important orchard pest. Its management has been based in chemical sprays, but biological control is a growing demand. The objective of this work was to evaluate, under laboratory conditions, the virulence of eight nematode isolates to A. fraterculus in a soil collected in Porto Amazonas, Paraná, Brazil, and to estimate lethal doses (LD50 and LD90) for the more virulent isolate. Steinernema carpocapsae CB 02, three Heterorhabditis sp., two H. amazonensis and two Oscheius sp. isolates were tested in laboratory against A. fraterculus third-instar larvae using as substrate a loam Cambisol collected in an apple orchard. S. carpocapsae CB 02 isolate caused the higher percent mortality of A. fraterculus. Heterorhabditis sp. isolates and LAMIP 9 (Oscheius sp.) isolates were intermediate, while LAMIP 92 (Oscheius sp.) didn't differ from the control. S. carpocapsae CB 02 is able to kill 50% and 90% of A. fraterculus population with 96.3 and 314.7 infective juveniles per larva, respectively, in that soil. As a conclusion, CB 02 is the most virulent to A. fraterculus when the substrate is Porto Amazonas' apple orchard soil and it is able to kill 50 and 90% larval population with 96.3 and 314.7 infective juveniles per larva, respectively.